The best results in athletic research - Peer, K. S. (Journal of Athletic Enhancement, 2020)
Exercise is a known stressor that has influence over many different physiological systems in the body. There is evidence in the literature that long-term training in athletes can negatively affect antimicrobial protein levels in the oral cavity. Furthermore, it has been reported that athletes face a higher incidence of upper respiratory tract infection (URTI) compared to more sedentary individuals. Based upon the reports in the literature, it is understood that long-term training for sport performance is a stressor that can both elevate physiological potential for in the athletic arena, but may depress function in other system. Moreira et al. reported that a 2-week detraining period after a competitive soccer season attenuated secretory IgA (sIgA) suppression and symptomology of URTI due to training. From this study it can be suggested that mucosal immunity can quickly rebound if rest and recovery are allowed for athletic populations. However, with the demands placed upon athletes, reduced mucosal immunity and risk for URTI are likely to remain an issue into the future.